Euclid preparation XXXVI. Modelling the weak lensing angular power spectrum - Deshpande, A. (EDP Sciences, 2025)
This work considers which higher order modeling effects on the cosmic shear angular power spectra must be taken into account for Euclid. We identified the relevant terms and quantified their individual and cumulative impact on the cosmological parameter inferences from Euclid. We computed the values of these higher order effects using analytic expressions and calculated the impact on cosmological parameter estimations using the Fisher matrix formalism. We reviewed 24 effects and determined the ones that potentially need to be accounted for, namely: the reduced shear approximation, magnification bias, source-lens clustering, source obscuration, local Universe effects, and the flat Universe assumption. After computing these effects explicitly and calculating their cosmological parameter biases, using a maximum multipole of l = 5000, we find that the magnification bias, source-lens clustering, source obscuration, and local Universe terms individually produce significant (> 0.25σ) cosmological biases in one or more parameters; accordingly, these effects must be accounted for and warrant further investigation. In total, we find biases in Ωm, Ωb, h, and σ 8 of 0.73σ, 0.28σ, 0.25σ, and -0.79σ, respectively, for the flat λCDM. For the w0waCDM case, we found biases in Ωm, Ωb, h, ns, σg, and wa of 1.49σ, 0.35σ, -1.36σ, 1.31σ, -0.84σ, and -0.35σ, respectively. These are increased relative to the ΛCDM due to additional degeneracies as a function of redshift and scale. © 2024 EDP Sciences. All rights reserved.